2018
DOI: 10.1158/2326-6066.cir-17-0343
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tissue Factor for Immunotherapy of Triple-Negative Breast Cancer Using a Second-Generation ICON

Abstract: Triple-negative breast cancer (TNBC) is a leading cause of breast cancer death and is often associated with and mutation. Due to the lack of validated target molecules, no targeted therapy for TNBC is approved. Tissue factor (TF) is a common yet specific surface target receptor for cancer cells, tumor vascular endothelial cells, and cancer stem cells in several types of solid cancers, including breast cancer. Here, we report evidence supporting the idea that TF is a surface target in TNBC. We used cancer lines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 60 publications
0
56
0
Order By: Relevance
“…VECs (64% of 14 patients with TNBC) 14 . In addition, our laboratory reported that TF is a novel oncotarget for CSCs, which were isolated from human breast, lung and ovarian cancer cell lines including TNBC, tumor xenografts and patients with breast cancer 15 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…VECs (64% of 14 patients with TNBC) 14 . In addition, our laboratory reported that TF is a novel oncotarget for CSCs, which were isolated from human breast, lung and ovarian cancer cell lines including TNBC, tumor xenografts and patients with breast cancer 15 .…”
mentioning
confidence: 99%
“…Besides its role as the primary initiator of coagulation, TF is also a modulator of pathological angiogenesis [24][25][26] . We and our collaborators along with other groups have identified TF as an angiogenesis-specific receptor on VEGF-stimulated angiogenic microvascular endothelial models in vitro as well as in vivo in angiogenic VECs (the inner layer) of the pathological neovasculature of endometriosis, age-related macular degeneration (AMD) and solid cancers, including melanoma 27,28 , lung cancer 29 and breast cancer 29 , and from tumor xenografts in mice and breast cancer tissues from patients 14,16 . In cancer, TF is highly expressed on the cancer cells in many types of solid cancers 14,23,[30][31][32] , acute myeloid and lymphoblastic leukemia (AML and ALL) and sarcoma 23,32 as well as in Hodgkin's lymphoma 33 and multiple myeloma (MM, TF detected in 10 out of 18 patients with MM and 3 MM lines) 34 .…”
mentioning
confidence: 99%
See 3 more Smart Citations